Architectural concretes for 3D construction printing - I. A. Stoletova (Cherepanova); A. A. Volodchenko (Вестник СибАДИ)
Introduction. One of the rising architectural trends of the present time is to increase the comfort and aesthetics of the territories of populated areas through artistic improvement, a significant role in which is given to various types of small architectural forms. The most budgetary and, at the same time, reliable and durable material for them is architectural concrete. The bottleneck in the use of concrete for the manufacture of small architectural forms is the relative difficulty of giving it complex spatial configurations. At the current level of development of concrete work technology, this drawback can be easily overcome through the use of construction 3D printing technology. The aim of the work was to develop effective architectural concrete for the manufacture of small architectural forms using the 3D construction printing method, based on composite binders containing weathered quartzite sandstones as a mineral additive, as one of the types of local energy-efficient raw materials. Materials and methods: The section presents comparative characteristics of weathered and unweathered quartzite sandstones.Results. The data on the dynamics of component grinding; compositions and characteristics of composite binders and fine-grained concretes based on them; results of manufacturing a pilot batch of small architectural forms using the construction printing method are presented.Discussion and conclusions. The description and analysis of the obtained experimental data are presented. The conclusions are formulated in which it is noted that for the organization of the production of modern small architectural forms, the technology of 3D construction printing is used, which allows the implementation of complex various spatial forms of products with any level of individualization without increasing costs. The developed molding mixtures confirmed the high efficiency of using weathered quartzite sandstone as part of a composite binder and technogenic sand. The introduction of the developed materials meets the requirements of energy and resource conservation, since the consumption of Portland cement and non-renewable natural resources is reduced.